Responsivitas Masyarakat Terhadap Manajemen Pelayanan Perpajakan Dalam Pembuatan Nomor Pokok Wajib Pajak (NPWP) Di Kantor Pelayanan Pajak (KPP) Pratama Sorong - Sardju, Arimbi; Akmal, Samsul; Hidayat, Rahmat Al (STIA Bengkulu, 2024)
This research aims to determine the public's response in measuring the management of Taxpayer Identification Number services provided by the Pratama Sorong Tax Service Office (KPP). The research method uses a quantitative descriptive approach. The number of respondents involved was 100 people. The results of the research show that the KPP Pratama service management indicator that gets the highest score from community responsiveness in making NPWPs is the “Reliability” factor, with an average score of 9.18 and is at the